(untitled) (International journal of artificial intelligence, 2026)
This article provides a comprehensive historical and economic analysis of tourism development in the United Kingdom, focusing on growth dynamics, institutional frameworks, and strategic policy directions in the early 21st century. The study incorporates all available statistical data on tourist flows, financial indicators, and employment generation, while also expanding on their broader economic implications. Particular attention is given to the activities of Visit Britain, the implementation of differentiated marketing strategies, and the role of government-led initiatives such as the “Great Britain” campaign. The article further evaluates tourism as a key driver of economic growth and examines its transformation into a leading sector of the national economy.